Through the Looking-Glass: A Scoping Review of Psychological Mechanisms of Psychedelic-Assisted Therapy for Substance Use Disorders - Kathryn Fletcher; Jack Freestone; Nadine Ezard; Elizabeth Knock; Krista J. Siefried (Current Addiction Reports, 2026)
Abstract Purpose of Review Psychedelic-assisted therapy (PAT) has re-emerged as a potential intervention for substance use disorders (SUDs), yet the psychological mechanisms underlying behaviour change remain poorly synthesised. This scoping review mapped and evaluated proposed psychological processes underpinning PAT in adults with SUDs. Recent Findings Peer-reviewed English-language empirical studies involving adults with SUDs or harmful substance use that examined psychological mechanisms of PAT were eligible for inclusion. Systematic searches of Embase, PubMed, PsycINFO and Scopus were conducted through 30 June 2026. Data were charted using a predefined extraction framework. Thirty-seven publications representing 23 unique cohorts ( n = 1003) met the inclusion criteria. Across studies of classical (psilocybin, ayahuasca) and non-classical psychedelics (ketamine, MDMA, ibogaine), six transdiagnostic mechanism domains were identified: (1) emotional processing, (2) insight, meaning-making and worldview change, (3) self-experience and identity transformation, (4) mystical or peak-type experiences, (5) relational and interpersonal shifts, and (6) motivation, values and behavioural regulation. Evidence ranged from qualitative and exploratory quantitative findings to preliminary quantitative studies explicitly examining associations between candidate psychological mechanisms and substance use outcomes. Mystical-type experiences were the most frequently examined and were associated with reductions in substance use and craving, although evidence remains largely correlational, with only one randomised trial demonstrating mediation. Qualitative findings highlighted the importance of therapeutic, relational, and sociocultural context in translating acute psychedelic experiences into psychological and behavioural change. Summary PAT appears to operate through interacting psychological processes rather than a single mechanism. Although recent studies have begun to explicitly examine candidate psychological mechanisms in relation to substance use outcomes, causal mechanisms remain to be established. Clarifying these mechanisms across populations and psychedelic compounds will be critical for optimising treatment models and guiding future research.